2002
DOI: 10.1002/eat.10086
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the relationship between mood and binge eating in the natural environment using ecological momentary assessment

Abstract: This study provides evidence that the affective experience of binge eating, when assessed in the natural environment, is negative. Furthermore, there was no evidence that binge eating was a response to an immediate or transient negative mood state or that binge eating provided relief from negative mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 18 publications
13
96
1
2
Order By: Relevance
“…First, the assessment schedule was limited to the least burdensome schedule that would still adequately capture variability in NSSI and DE. Previous micro-longitudinal studies have used a two-week monitoring period to observe DE (Goldschmidt et al, 2014;Smyth et al, 2007;Wegner et al, 2002) and NSSI (Nock et al, 2009), and have demonstrated that NSSI and DE typically occur a few times per week. Thus, we expected that the primary behaviors of interest could be accurately recalled in daily reports, rather than requiring more frequent daily assessments.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the assessment schedule was limited to the least burdensome schedule that would still adequately capture variability in NSSI and DE. Previous micro-longitudinal studies have used a two-week monitoring period to observe DE (Goldschmidt et al, 2014;Smyth et al, 2007;Wegner et al, 2002) and NSSI (Nock et al, 2009), and have demonstrated that NSSI and DE typically occur a few times per week. Thus, we expected that the primary behaviors of interest could be accurately recalled in daily reports, rather than requiring more frequent daily assessments.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…longitudinal studies of NSSI and DE, which have relied on samples of 27 to 36 participants (Armey et al, 2011;Nock et al, 2009;Shingleton et al, 2013;Wegner et al, 2002), replication in larger and more diverse samples is needed. A second limitation arose because NSSI and DE were assessed only once per day and irrespective of time at which the behavior occurred.…”
Section: Co-occurring Non-suicidal Self-injury and Disordered Eating 19mentioning
confidence: 99%
“…25 In adolescents, emotion-focused coping was found to be associated with disturbed eating attitudes 26 and to be predictive of a predisposition for developing an eating disorder. 27,28 In addition, data from different areas of research, e.g., ecological momentary assessment on adults with BED, bulimia nervosa, 2 and binge eating, 29,30 experimental studies on adults with BED, 31,32 and intervention studies on patients with BED [33][34][35] suggest that binge eating is associated with problematic emotion regulation. Early studies showed that eating psychopathology was associated with an increased use of maladaptive coping and a decreased use of adaptive coping in a nonclinical population 36 and in adults with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Bolger, Davis, and Rafaeli (2003) provide a review of the benefits of such programs, including timestamps for responses, flexibility in presentation of questions, and more efficient data entry and management. Recent studies have used electronic handheld devices to investigate physical symptoms (e.g., physical anxiety symptoms; Pfaltz, Michael, Grossman, Margraf, & Wilhelm, 2010;Smyth & Stone, 2003), behaviors such as alcohol consumption (Collins et al, 1998;Hufford, Shields, Shiffman, Paty, & Balabanis, 2002;Kashdan, Ferssizidis, Collins, & Muraven, 2010;Simons, Dvorak, Batien, & Wray, 2010;Swendsen et al, 2000), drug use (Buckner, Crosby, Silgado, Wonderlich, & Schmidt, 2012;Buckner et al, 2011), eating disorder symptoms (Engel et al, 2007;le Grange, Gorin, Dymek, & Stone, 2002;Muehlenkamp et al, 2009;Wegner et al, 2002), and psychological constructs such as affect (Juth, Smyth, & Santuzzi, 2008;Trull et al, 2008), mood disorders/depressive symptoms (aan het Rot, Hogenelst, & Schoevers, 2012;Vranceanu, Gallo, & Bogart, 2009;Wenze & Miller, 2010), self-esteem (Kernis, 2005), social anhedonia and social anxiety (Brown, Silvia, Myin-Germeys, & Kwapil, 2007;Buckner, Crosby, Wonderlich, & Schmidt, 2012), and anxiety symptoms in general (Gallagher, Schoemann, & Pressman, 2011). A recent review has highlighted the use of electronic EMA as a part of psychosocial and health behavior interventions (Heron & Smyth, 2010).…”
Section: Handheld Devicesmentioning
confidence: 99%